Two phases fermentative process for hydrogen and methane production from cassava wastewater - Oliveira, Aryane Mota; Amorim, Norma Candida dos Santos; Amorim, Eduardo Lucena Cavalcante; Salomon, Karina Ribeiro (Journal of Health & Biological Sciences, 2017)
Introduction: Hydrogen and methane production was investigated in two phases of fermentative process. Objective: At the acidogenic phase, an anaerobic fluidized bed reactor was fed with cassava wastewater producing hydrogen. Methods: Expanded clay was used as a support material for biomass immobilization. The reactor was operated with HRT ranging from 8-1 h. Results: The best hydrogen yield production was 1.91 mol H2/mol glucose at HRT of 2 h. At the methanogenic phase, the acidogenic process effluent fed a fixed-bed reactor producing methane. Conclusion: Sururu (Mytella falcata) shells was used as support acted as pH neutralizer in the fixed-bed reactor, yielding best (0.430±0.150 Lmethane/gCOD) with 12h HRT phase.